Capital social e uso de serviços odontológicos em adultos e idosos no Brasil - Campagnol, Patrícia Bastianello (2021)
Although there is evidence on inequalities in the use of general health services, it is still necessary to explore the experiences of adults and elderly people in the use of dental services, especially the influence of social capital. Most of these studies refer to developed countries, it is believed that there is no study with the population of Brazil using a national representative sample, especially with the population of adults and elderly. The aim of this study is to assess the prevalence of the use of dental services and the association of social capital among Brazilian adults and elderly people. This is a cross-sectional study with data from the Longitudinal Study of the Health of Brazilian Elderly People, which is a population-based, nationally representative study of people aged 50 or over, carried out between 2015 and 2016. The sample consisted of 9,323 individuals and data collection was carried out through structured questionnaires. The outcome was Use of dental service in the last year. The main predictor was social capital, through two dimensions: structural and cognitive. The other independent variables were: sex, skin color, age, education, wealth, depression, life satisfaction, need for dental treatment, self-perception of oral health, tooth loss, type of dental service, reason for dental care, smoking use and alcohol use. Statistical analysis was performed using Poisson regression with svy command for complex samples. The prevalence of use of dental services in the last year was 32.6% (95%CI: 30.7-34.5). No associations were found between social capital and the use of dental services. It is possible that numerous factors have influenced the results, from limitations in measuring social capital, through characteristics of the work process of health services, to issues related to the elderly population and its cultural and biological characteristics that influence oral health. It is necessary that new studies are carried out, with different designs, variables and approaches.